The Influence of Discovery Learning Strategy on Learning Engagement and Knowledge Construction in Asynchronous Online Learning - Abuddar; Chusnul Muali (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Asynchronous online learning offers flexibility in time and pace; however, it is frequently associated with low student engagement and superficial knowledge construction. This study aims to examine the effect of discovery learning strategies on students’ learning engagement and knowledge construction in an asynchronous learning environment. A quantitative quasi-experimental design with a posttest-only control group was employed, involving 64 tenth-grade students of SMA Nurul Jadid, divided into an experimental group (n = 32) and a control group (n = 32). The experimental group engaged with Moodle-based modules structured according to discovery learning stages, while the control group used conventional expository modules over four learning sessions on the topic of prayer. Data were collected using an adapted Student Engagement Scale (Cronbach’s alpha = 0.87) and an analytical rubric to assess knowledge construction (inter-rater reliability = 0.85). Multivariate analysis (MANOVA) revealed a significant difference between the groups (Pillai’s Trace = 0.520; F(2, 61) = 33.006; p < 0.001). Univariate results indicated that the experimental group achieved higher learning engagement (M = 82.45, SD = 6.12) than the control group (M = 70.10, SD = 7.45), F(1, 62) = 52.505; p < 0.001, and demonstrated superior knowledge construction (M = 85.20, SD = 5.89) compared to the control group (M = 72.35, SD = 8.10), F(1, 62) = 52.680; p < 0.001. These findings conclude that discovery learning is an effective instructional strategy for enhancing engagement and fostering deeper, more meaningful knowledge construction in asynchronous online learning environments.